2020
DOI: 10.1007/s00402-020-03492-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of bi-unicompartmental knee arthroplasty for both medial and lateral femorotibial arthritis: a systematic review—is there proof of concept?

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
0
14
0
1
Order By: Relevance
“…They reported a 100% graft survival with a mean follow-up of 24 months. More recently, Gilat et al [81] evaluated 36 patients younger than 18 years, with a mean follow-up of 4.6 years. They found a failure rate of 5.6% and a re-operation rate of 28.8%.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a 100% graft survival with a mean follow-up of 24 months. More recently, Gilat et al [81] evaluated 36 patients younger than 18 years, with a mean follow-up of 4.6 years. They found a failure rate of 5.6% and a re-operation rate of 28.8%.…”
Section: Discussionmentioning
confidence: 99%
“…27 Alongside gait analysis, proprioception metrics are reviewed to compare cruciate-retaining bi-unicompartmental knee arthroplasty (bi-UKA) with a cruciate-sacrificing TKA approach. Wada et al 28 have reviewed the sparse literature on simultaneous bi-UKA, and concluded that there was a need for further studies, such as this one, to determine the efficacy of two UKAs as an alternative to TKA with isolated degeneration in the condyles and an intact ACL.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] One-third of people with knee OA have damage limited to just two compartments of the knee, 4 and as such there has been a renewed interest in combined partial knee arthroplasty (CPKA) to treat knee OA in a limited manner. [5][6][7][8][9][10][11][12][13][14] In particular, bi-unicondylar arthroplasty (Bi-UKA) is of interest for patients with a healthy patellofemoral compartment and functional cruciate ligaments, and either ipsilateral medial and lateral tibiofemoral OA, 4,5,11,12 or a well-functioning unicondylar arthroplasty (UKA) with subsequent degeneration in the other tibiofemoral compartment. 13 Recent evidence suggests that Bi-UKA patients have superior outcomes and biomechanics compared to those with a similar disease pattern but treated with total knee arthroplasty (TKA).…”
Section: Introductionmentioning
confidence: 99%